2020
DOI: 10.3390/ijms21062024
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Hyperplasia, Hormonal Changes and Prolactinoma Development in Males Exposed to Estrogens—An Insight From Translational Studies

Abstract: Estrogen signaling plays an important role in pituitary development and function. In sensitive rat or mice strains of both sexes, estrogen treatments promote lactotropic cell proliferation and induce the formation of pituitary adenomas (dominantly prolactin or growth-hormone-secreting ones). In male patients receiving estrogen, treatment does not necessarily result in pituitary hyperplasia, hyperprolactinemia or adenoma development. In this review, we comprehensively analyze the mechanisms of estrogen action u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 142 publications
(220 reference statements)
0
8
0
Order By: Relevance
“…It is well known that estrogen stimulates the pituitary stem/progenitor cell differentiation in the direction of a lactotrophic cell line. 60 In addition, it has been reported that estrogen regulates the SC of the human reproductive system, which induces SC proliferation and participates in the regulation of SC populations in a paracrine manner. 61 In summary, we have analyzed the expression of SC/TSC markers at different stages of hyperplastic/adenomatous pituitary development.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that estrogen stimulates the pituitary stem/progenitor cell differentiation in the direction of a lactotrophic cell line. 60 In addition, it has been reported that estrogen regulates the SC of the human reproductive system, which induces SC proliferation and participates in the regulation of SC populations in a paracrine manner. 61 In summary, we have analyzed the expression of SC/TSC markers at different stages of hyperplastic/adenomatous pituitary development.…”
Section: Discussionmentioning
confidence: 99%
“…In prolactinomas, tumor growth related to oral estrogen therapy has already been re-ported, since these types of tumors present a significant ER expression [ 88 , 89 ]. An important role might also be played, especially in males, by the intra-tumoral activity of aromatase, which locally transforms testosterone into estradiol [ 90 ].…”
Section: Clinical Use Of Estrogens And/or Serms In Patients With Acro...mentioning
confidence: 99%
“…Dopamine inhibits proliferation of lactotroph cells, prolactin synthesis and release, acting via the D2R expressed in lactotroph cells [20]. Estrogen hormones may contribute to pathogenesis of prolactinomas, as these tumors grow faster during pregnancy and develop in transsexual men under estrogen treatment [23,24]. Estradiol and estrogens in general decrease the effects of dopamine agonists, induce prolactin gene transcription and indirectly lower dopamine synthesis from the hypothalamus [6,20,25].…”
Section: Molecular Pathogenesis Of Prolactinomas Important To Design Future Treatments Estrogenmentioning
confidence: 99%